IL-2 administration increases CD4(+)CD25(hi) Foxp3(+) regulatory T cells in cancer patients - Ahmadzadeh, Mojgan (The American Society of Hematology, 2006)
Interleukin-2 (IL-2) is historically known as a T-cell growth factor. Accumulating evidence from knockout mice suggests that IL-2 is crucial for the homeostasis and function of CD4(+)CD25(+) regulatory T cells in vivo. However, the impact of administered IL-2 in an immune intact host has not been studied in rodents or humans. Here, we studied the impact of IL-2 administration on the frequency and function of human CD4(+)CD25(hi) T cells in immune intact patients with melanoma or renal cancer. We found that the frequency of CD4(+)CD25(hi) T cells was significantly increased after IL-2 treatment, and these cells expressed phenotypic markers associated with regulatory T cells. In addition, both transcript and protein levels of Foxp3, a transcription factor exclusively expressed on regulatory T cells, were consistently increased in CD4 T cells following IL-2 treatment. Functional analysis of the increased number of CD4(+)CD25(hi) T cells revealed that this population exhibited potent suppressive activity in vitro. Collectively, our results demonstrate that administration of high-dose IL-2 increased the frequency of circulating CD4(+)CD25(hi) Foxp3(+) regulatory T cells. Our findings suggest that selective inhibition of IL-2-mediated enhancement of regulatory T cells may improve the therapeutic effectiveness of IL-2 administration. (Blood. 2006;107:2409-2414)